208k views
3 votes
What is the solution to the following system of equations?

y = 6x - 11
-2x - 3y = -7

A. -13/10, -94/5
B. -1/2, -14
C. (1, –5)
D. (2, 1)

2 Answers

4 votes

Answer:

D

Explanation:

Given the 2 equations

y = 6x - 11 → (1)

- 2x - 3y = - 7 → (2)

Substitute y = 6x - 11 into (2)

- 2x - 3(6x - 11) = - 7 ← distribute and simplify left side

- 2x - 18x + 33 = - 7

- 20x + 33 = - 7 ( subtract 33 from both sides )

- 20x = - 40 ( divide both sides by - 20 )

x = 2

Substitute x = 2 into (1) for corresponding value of y

y = 6(2) - 11 = 12 - 11 = 1

solution is (2, 1 ) → D

User Tomasz Maj
by
6.5k points
5 votes

Answer:

D.(2,1)

Explanation:

All I did was solve by substitution.

User DaveMorganTexas
by
6.5k points